Role of primary sensory neurone cannabinoid type-1 receptors in pain and the analgesic effects of the peripherally acting agonist CB-13 in mice. (January 2022) - Ford, Neil C.; Barpujari, Awinita; He, Shao-Qiu; Huang, Qian; Zhang, Chi; Dong, Xinzhong; Guan, Yun; Raja, Srinivasa N.
Abstract: Background: Cannabinoid type-1 receptors (CB1 Rs) are expressed in primary sensory neurones, but their role in pain modulation remains unclear. Methods: We produced Pirt -CB1 R conditional knockout (cKO) mice to delete CB1 Rs in primary sensory neurones selectively, and used behavioural, pharmacological, and electrophysiological approaches to examine the influence of peripheral CB1 R signalling on nociceptive and inflammatory pain. Results: Conditional knockout of Pirt -CB1 R did not alter mechanical or heat nociceptive thresholds, complete Freund adjuvant-induced inflammation, or heat hyperalgesia in vivo . The intrinsic membrane properties of small-diameter dorsal root ganglion neurones were also comparable between cKO and wild-type mice. Systemic administration of CB-13, a peripherally restricted CB1 /CB2 R dual agonist (5 mg kg −1 ), inhibited nociceptive pain and complete Freund adjuvant-induced inflammatory pain. These effects of CB-13 were diminished in Pirt -CB1 R cKO mice. In small-diameter neurones from wild-type mice, CB-13 concentration-dependently inhibited high-voltage activated calcium current (HVA-ICa ) and induced a rightward shift of the channel open probability curve. The effects of CB-13 were significantly attenuated by AM6545 (a CB1 R antagonist) and Pirt -CB1 R cKO. Conclusion: CB1 R signalling in primary sensory neurones did not inhibit nociceptive or inflammatory pain, or the intrinsic excitability of nociceptive neurones. However, peripheral CB1 Rs are important for the analgesic effects of systemically administered CB-13. In addition, HVA-ICa inhibition appears to be a key ionic mechanism for CB-13-induced pain inhibition. Thus, peripherally restricted CB1 R agonists could have utility for pain treatment.